1988
DOI: 10.1113/jphysiol.1988.sp017171
|View full text |Cite
|
Sign up to set email alerts
|

On the potassium conductance increase activated by GABAB and dopamine D2 receptors in rat substantia nigra neurones.

Abstract: SUMMARY1. Intracellular recordings were made from 193 substantia nigra zona compacta neurones in slices of rat mesencephalon. All cells were hyperpolarized by baclofen; this was accompanied by a fall in input resistance. Cells voltage clamped at -60 mV showed an outward current associated with a conductance increase in response to baclofen. The baclofen effects were concentration dependent (effective range 0 3-30 lM); the concentration producing half the maximal effect was 1P5 ,UM. (-)-Baclofen was 300-700 tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
216
1
2

Year Published

1990
1990
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 324 publications
(244 citation statements)
references
References 27 publications
25
216
1
2
Order By: Relevance
“…Furthermore, the apparent independence of the outward tolbutamide-sensitive current caused by dialysis with ATP-free solutions and the baclofen outward current (Fig. 5B) is direct evidence that the potassium current regulated by intracellular ATP and that gated by both GA-BA, and D, receptors (Lacey et al, 1988) utilize different sets of channels. Thus, although in several other cell types G-protein-coupled receptors may be able to operate potassium channels gated by intracellular ATP (Zhang et al, 1994; and see Edwards and Weston, 1993, for review), this has yet to be unequivocally demonstrated in dopamine neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the apparent independence of the outward tolbutamide-sensitive current caused by dialysis with ATP-free solutions and the baclofen outward current (Fig. 5B) is direct evidence that the potassium current regulated by intracellular ATP and that gated by both GA-BA, and D, receptors (Lacey et al, 1988) utilize different sets of channels. Thus, although in several other cell types G-protein-coupled receptors may be able to operate potassium channels gated by intracellular ATP (Zhang et al, 1994; and see Edwards and Weston, 1993, for review), this has yet to be unequivocally demonstrated in dopamine neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary reports from RBper and colleagues, using both whole-cell "perforated patch" clamp and single-channel recording from enzymatically isolated cells of adult guinea pig SN, suggested that dopamine cells possessed potassium channels that opened when extracellular glucose was removed or, in inside-out patches, when intracellular ATP was removed, and could be closed by the sulfonylurea tolbutamide (Rijper et al, 1990a,b). Furthermore, the hyperpolarization caused by both dopamine and baclofen was reported to be blocked by tolbutamide (RBper et al,199Oc), suggesting that the K-ATPs and the potassium channels gated by GABA, and D, receptors (Lacey et al, 1988) were one and the same. Another whole-cell patch-clamp study on dissociated rat SN neurons reported that dopamine neurons were hyperpolarized following dialysis with an intracellular solution containing no added ATP (but not with 2 mM ATP), and also by application of high concentrations of the KCAs cromakalim and pinacidil.…”
mentioning
confidence: 99%
“…The blockade of the long lasting pargyline-induced inhibitory effects by the selective D2/3-receptor antagonist, (-)-sulpiride and the lack of additional actions of the DI antagonist, SCH 23390 suggest that the pargyline-induced inhibition is mainly the consequence of activation of D2/3 dopamine autoreceptors by endogenous nondegraded dopamine. Thus, the indirect activation of these somatodendritic autoreceptors inhibits the principal neurones by hyperpolarizing the membrane via an increase of potassium conductance (Lacey et al, 1987;1988). Since we had to use high and unspecific concentrations of both clorgyline and Ldeprenyl to observe consistent acute effects on firing discharge, it can be argued that a simple inhibition of MAO A or B activity does not produce a significant elevation of extracellular dopamine to activate the dopaminergic autoreceptors.…”
Section: Discussionmentioning
confidence: 99%
“…However, if one assumes that cocaine inhibits an uptake process showing typical Michaelis-Menten properties, then the effective concentration of cocaine would depend on the ambient concentration of dopamine. There are no direct measurements that have compared the extracellular dopamine concentration in vivo and in vitro; all that can be said is that the similar pattern of firing of the neurones in the two circumstances (Lacey et al, 1987;Grace & Bunney, 1983) & Lacey, 1988;Pan & Williams, 1989). In the locus coeruleus, the threshold concentration is about 1 gM and in the dorsal raphe about 300 nm.…”
Section: Cocaine Inhibits Cellfiring By Blocking Dopamine Uptakementioning
confidence: 99%